Variations Of Thermoregulation And Motor Skills For Athletes During The Fasting Month Of Ramadan - Hakkoumi , Ali (sports creativity, 2025)
Variations of the thermoregulation and the working capacity for athletes during the fasting month of Ramadan Summary Our research had the objective to study in a group of athletes, the influence of fasting month -Ramadan on the physical performance and the balance of the thermoregulation. In this context, the scientific studies highlight the dangers of the dehydration. What are the pre-cautions to be taken by the Muslim sportsmen who participate in official competitions during the fast of Ramadan? Question for which there are until now no determined methodological direc-tives Through our research, it is supposed that a diurnal and total alimentary abstinence, particularly hydric was a source of disturbances, causing a negative influence on the physical performance and the thermoregulation balance. Our experimentation concerned a group of 13 male athletes, of military athletics national team aged between 21 and 33 years old. This group of athletes has been tested on a race event of 3000 meters, and that 11 days before the period of Ramadan, 25th day during the fast period, and 119th day after the fast of Ramadan. These tests were accompanied with the measures of axillary temperature before and immediately after the realization of every test. These athletes followed an individualized training program, and the tests were conducted during the general physical prepa-ration period In the term of the research, it was noticed a regression of the average of the physical performanc-es in running and an increase amplitude of the axillary temperature during the period of fast. The study allowed to deduct that the diurnal food abstinence particularly the hydric privation, decreased the physical performance of middle-distance race and increase the axillary temperature during the period of fast, what inevitably leads towards a state of dehydration where the sports-man can expose his health to consequences which can be grave.